Preliminary Assessment of the Anti-inflammatory Activity of New Structural Honokiol Analogs with a 4′-O-(2-Fluoroethyl) Moiety and the Potential of Their 18F-Labeled Derivatives for Neuroinflammation Imaging - Daria D. Vaulina; Kira I. Stosman; Konstantin V. Sivak; Andrey G. Aleksandrov; Nikolai B. Viktorov; Nikolay N. Kuzmich; Mariia M. Kiseleva; Olga F. Kuznetsova; Natalia A. Gomzina (Molecules, 2021)
Neolignans honokiol and 4′-O-methylhonokiol (MH) and their derivatives have pronounced anti-inflammatory activity, as evidenced by numerous pharmacological studies. Literature data suggested that cyclooxygenase type 2 (COX-2) may be a target for these compounds in vitro and in vivo. Recent studies of [11C]MPbP (4′-[11C]methoxy-5-propyl-1,1′-biphenyl-2-ol) biodistribution in LPS (lipopolysaccharide)-treated rats have confirmed the high potential of MH derivatives for imaging neuroinflammation. Here, we report the synthesis of four structural analogs of honokiol, of which 4′-(2-fluoroethoxy)-2-hydroxy-5-propyl-1, 1′-biphenyl (F-IV) was selected for labeling with fluorine-18 (T1/2 = 109.8 min) due to its high anti-inflammatory activity confirmed by enzyme immunoassays (EIA) and neuromorphological studies. The high inhibitory potency of F-IV to COX-2 and its moderate lipophilicity and chemical stability are favorable factors for the preliminary evaluation of the radioligand [18F]F-IV in a rodent model of neuroinflammation. [18F]F-IV was prepared with good radiochemical yield and high molar activity and radiochemical purity by 18F-fluoroethylation of the precursor with Boc-protecting group (15) with [18F]2-fluoro-1-bromoethane ([18F]FEB). Ex vivo biodistribution studies revealed a small to moderate increase in radioligand uptake in the brain and peripheral organs of LPS-induced rats compared to control animals. Pretreatment with celecoxib resulted in significant blocking of radioactivity uptake in the brain (pons and medulla), heart, lungs, and kidneys, indicating that [18F]F-IV is likely to specifically bind to COX-2 in a rat model of neuroinflammation. However, in comparison with [11C]MPbP, the new radioligand showed decreased brain uptake in LPS rats and high retention in the blood pool, which apparently could be explained by its high plasma protein binding. We believe that the structure of [18F]F-IV can be optimized by replacing the substituents in the biphenyl core to eliminate these disadvantages and develop new radioligands for imaging activated microglia.